2023
DOI: 10.3390/ijerph20116049
|View full text |Cite
|
Sign up to set email alerts
|

Treponema denticola Has the Potential to Cause Neurodegeneration in the Midbrain via the Periodontal Route of Infection—Narrative Review

Abstract: Alzheimer’s disease (AD) is a neurodegenerative disease and the most common example of dementia. The neuropathological features of AD are the abnormal deposition of extracellular amyloid-β (Aβ) and intraneuronal neurofibrillary tangles with hyperphosphorylated tau protein. It is recognized that AD starts in the frontal cerebral cortex, and then it progresses to the entorhinal cortex, the hippocampus, and the rest of the brain. However, some studies on animals suggest that AD could also progress in the reverse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 158 publications
1
0
0
Order By: Relevance
“…We are of the opinion that HIV positive individuals having the preceding attributes are potentially likely to display lower IQ scores. Our opinion is further supported by the observations of some authors who have shown that oral colonization with microorganisms such as Treponema denticola, is associated with cognitive impairment (Pisani et al, 2022;Tang et al, 2022;Pisani et al, 2023). In a context of HIV infection, and when considering C. albicans as the microorganism of interest, the preceding outcome is potentially also likely.…”
Section: Perspectivessupporting
confidence: 76%
“…We are of the opinion that HIV positive individuals having the preceding attributes are potentially likely to display lower IQ scores. Our opinion is further supported by the observations of some authors who have shown that oral colonization with microorganisms such as Treponema denticola, is associated with cognitive impairment (Pisani et al, 2022;Tang et al, 2022;Pisani et al, 2023). In a context of HIV infection, and when considering C. albicans as the microorganism of interest, the preceding outcome is potentially also likely.…”
Section: Perspectivessupporting
confidence: 76%